The Actualization of Pancasila Values as an Effort to Preserve Indonesian as a National Identity - Muhammad Parwis Halim (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Pancasila is believed to be a weltanschauung (an outlook on life), meaning that the values of Pancasila constitute the ethics of communal life of the Indonesian nation that have existed since long ago. Pancasila is the result of a crystallization drawn directly from the authentic life of Indonesian society. The actualization of Pancasila's values must be regarded as highly important for preserving the existence of Indonesian as a National Identity. The noble values contained in Pancasila should genuinely serve every citizen as a safeguard and as a distinguishing characteristic from other nations. The results of this study show that using and preserving Indonesian in daily life is a form of love for the homeland, and that a correct understanding of the values of Pancasila will encourage citizens to take part in safeguarding National Identity.